2007
DOI: 10.1088/0957-4484/18/18/185604
|View full text |Cite
|
Sign up to set email alerts
|

Formation studies and controlled production of carbon nanohorns using continuousin situcharacterization techniques

Abstract: The formation of carbon nanohorns by laser ablation was investigated using a scanning differential mobility analyzer combined with an ultrafine condensation particle counter. The measurement technique provided time-resolved size distributions for the carbon nanoparticles every minute during the course of the production run. The instrument performance was reasonably stable most of the time; however, during laser ablation, shockwave oscillations leading to significant transient flow and pressure variations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Single-wall carbon nanohorns (SWNHs) were produced by high-power Nd:YAG laser vaporization of pure graphite into background Ar gas at high temperature (1100 C) as described previously. [38] The short-SWNHs (s-SWNHs) used in these studies were produced by minimizing the laser pulse widths (0.5-ms, 4.5 J/pulse, 80Hz), yielding nanohorns with individual lengths < 10nm and roughly spherical aggregates with diameters typically between 40–60 nm, as assessed by high-resolution transmission electron microscopy (Hitachi, HF-3300 at 300kV). The growth time above 1000°C was limited to 8 ms, followed by several seconds annealing time at 1000°C within the tube furnace.…”
Section: Methodsmentioning
confidence: 99%
“…Single-wall carbon nanohorns (SWNHs) were produced by high-power Nd:YAG laser vaporization of pure graphite into background Ar gas at high temperature (1100 C) as described previously. [38] The short-SWNHs (s-SWNHs) used in these studies were produced by minimizing the laser pulse widths (0.5-ms, 4.5 J/pulse, 80Hz), yielding nanohorns with individual lengths < 10nm and roughly spherical aggregates with diameters typically between 40–60 nm, as assessed by high-resolution transmission electron microscopy (Hitachi, HF-3300 at 300kV). The growth time above 1000°C was limited to 8 ms, followed by several seconds annealing time at 1000°C within the tube furnace.…”
Section: Methodsmentioning
confidence: 99%
“…Single wall carbon nanohorns (SWCNHs) were synthesized using high power laser vaporization setup as described early [37,38]. Briefly, the experimental setup includes a quartz tube reactor mounted inside a tube furnace operating at 1150C with flowing Argon (flow rate ~ 4600 sscm) at atmospheric pressure.…”
Section: Synthesis and Characterization Of Swcnhsmentioning
confidence: 99%
“…Diagnostics of the synthesis process, as shown in Fig. 7.5b, have been performed to characterize the growth environment [39][40][41], and it has been shown that SWNHs grow at *1 nm/ms growth rates (equivalent to the 1 lm/s growth rate of SWNTs with catalyst-assistance) [42].…”
Section: Single-wall Carbon Nanohornsmentioning
confidence: 99%